Decolorization of Textile Dyes in a Fixed‐Bed Biofilm Reactor. Issue 6 (29th April 2022) - Madhushika, H. Gimhani; Ariyadasa, Thilini U.; Gunawardena, Sanja H. P.
Abstract: A fixed‐bed biofilm reactor (FBBR) was developed and its performance in decolorizing synthetic dye mixtures and textile industry effluents was evaluated in both batch and continuous modes. It was observed that yeast extract was important as the carbon source in the FBBR feed for color removal. However, the requirement for yeast extract in FBBR is very small compared to that in suspended cell cultures. Structural changes in dyes due to biological treatment were assessed from ultraviolet‐visible spectral and high‐performance liquid chromatography (HPLC) analyses. Gas chromatography‐mass spectrophotometry (GC‐MS) investigations confirmed that the metabolites formed were nontoxic and benign. Abstract : The ability of a bacterial biofilm to decolorize a synthetic dye mixture and textile industry effluent in a laboratory fixed‐bed biofilm reactor in both batch and continuous modes was investigated. The biofilms of a bacterial consortium grown on polypropylene cylindrical tubes resulted in effective color removals in the decoloration medium with yeast extract as the important carbon source.